LARANGAN PENGASINGAN TANAH DALAM HUKUM ADAT PERSPEKTIF HUKUM AGRARIA NASIONAL - I Made Suwitra (Fakultas Hukum Universitas Surabaya, 2018)
Adat Lands as a communal lands nowadays are helds individually. Adat lands in the forms of